El hacinamiento carcelario y los derechos humanos, un estudio desde Ecuador - Toledo Abarca, Luis Alexander (2023)
This research paper addresses the issue of prison overcrowding and its impact on human rights in Ecuador. It stresses on the need to update the infra-constitutional legal framework in Ecuador to adapt it to social advances and the evolution of human rights. The critical and documentary approach used for this research, seeks to overcome the problem of prison overcrowding and to ensure the rights established in the Constitution for people held in confinement, improving their social coexistence and achieving a dignified rehabilitation. The methodology used was descriptive, not experimental and cross-sectional, incorporating a mixed approach (qualitative-quantitative), as well as the methods; inductive-deductive, historical- logical, analytical-synthetic, corporate and dogmatic. In addition, various techniques were used, such as bibliographic review, signing, documentary review and a survey, applied on judges and lawyers from the Loja Canton. The results revealed that the causalistic system used in processes of imprisonment is not of last resort, which leads to the violation of the people held in confinement’s rights. Therefore, legislative reform is proposed in Ecuador to achieve true social rehabilitation and guarantee the fundamental rights of people held in confinement, addressing the problem of prison overcrowding and its negative impact on the country's prison system.